Industrial quality control study East Bay Impex Glass Corporation - Cando, Kim; Lanante, Rinacina Tatiana; Penaflorida, Karen Kristine (Diliman, Quezon City College of Engineering, 2004)
East Bay Impex Glass Corp. (EBIGC) is one of the few glass-manufacturing companies here in the Philippines. Although it has its share of its customers with its growing product line, it consumes a high labor expense due to excessive number of nonconformities. This is one of the reasons why the group became interested with the company. Also, EBIGC is one of the few production companies that do not automate its production process. It is purely manual labor handling the labor-intensive procedures in the manufacturing process, i.e. hand-blowing. The proponents conducted plant visits so as to view the actual work setting of the company. The group used historical records in gathering the necessary data, which in turn is used and presented in the report of the study. East Bay Impex Corp., produces numerous and diverse designs per day. However, product line 25106 Medium with Tail has the most number of orders and at the same time has the most number of rejects. A finished glass is rejected if it has one of the following nonconformities: bubbles, sand/stones embedded in the glass, scratches, uneven cut and broken lip. Through 100% visual inspection, the quality control inspector either accepts or rejects the item based on the mentioned nonconformities. Data from Jun-Aug 2003 revealed that the company produces 34% nonconforming for this particular item. To further reduce the percent nonconforming, the group identified several problem areas which they think contribute to the considerable high number rejects and recommended methods and procedures that may possibly improve the company process. To avoid the presence of sand/stones in the glass, it is recommended that the company do the washing/cleaning of the broken cullets themselves to ensure that stones are not mixed with it. They should maintain cleanliness of the loading area especially during raw material delivery. Formation of bubbles can be reduced by determining the exact loading time of raw materials so that molten glass keeps on flowing to the glory hole. The worker must also endure that there is correct gathering of the molten glass. The company should train their workers very well since glass blowing is a highly manual process. For the cutting operation, the cutting machine should have fixed settings to avoid the need for adjustments and thus producing glass with uneven cut. To prevent production of nonconforming items that are due to over fatigued workers, it is recommended that a work-rest cycle be implemented. The Production Manager should get an average number of good items that the workers produced before coming up with a rejected item. The Production Manager then schedules the worker to take a rest after producing his average. Scratches can be avoided by using plates that would support the product and would allow enough spacing between items. The temperature of the furnace is very crucial and should not be approximated. This is why it is also highly recommended that the company acquire a temperature gauge, preferably digital so that it is easy to operate and understand, to be able to monitor and control the exact temperature of the furnace. Lastly, to be able to determine the capability of the process, the company should set their lower and upper specification limits of fraction nonconforming. Implementation of the above recommendations will improve the quality of the company's production process and will greatly reduce the cost of nonconforming items.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: East Bay Impex Glass Corporation; Glass manufacture; Quality control